PENGARUH PARTISIPASI ANGGARAN, KEJELASAN SASARAN ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN KOMITMEN ORGANISASI DAN POLITIK ORGANISASI SEBAGAI VARIABEL MODERASI - Prihasantyo Siswo Nugroho; Tri Sumiyanti (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2017)
The process of budgeting involves many parties, including upperlevel managers to lower level managers. While to produce an effectivebudget, managers need the ability to predict the future, taking into accountvarious factors, such as participation, commitment and budget goalsthemselves. From various studies that have been done, there areinconsistencies from the results of research. The sample in this research ishead section, head of sub section, head of department and head of departmentinvolved in preparing the budget in each Satuan Kerja Pengawas Daerah(SKPD) of Central Java. The sample used is 20 SKPD with each SKPDconsisting of 20 echelon officials involved in budget preparation. To test thehypothesis proposed in this study, the data analysis technique used is to useStructural Equation Modeling (SEM) which is operated with AMOSprogram. With the result of research that partially budgetary participationand clarity of budget target have an effect on managerial performance, whilefor organizational politics moderation variable and organizationalcommitment able to strengthen influence of budget participation and clarityof budget target to managerial performance.